Dentofacial characteristics of patients with Angle Class I and Class II malocclusions - Rogério Lacerda dos Santos; Antônio Carlos de Oliveira Ruellas (Dental Press Editora, 2012)
OBJECTIVE: The present study assessed some cephalometric measurements of the soft tissue profile in order to observe the behavior of facial convexity in patients with Class I, Class II division 1, and Class II division 2 malocclusions. METHODS: One hundred and thirty pre-treatment teleradiographs of Caucasian patients aged 10-16 years (mean age of 12.6 years) were selected for study and divided into 3 groups. The cephalometric measurements used in the present study were the following: H.SN, Cx, NLA, MLA, UL-SUL-S, LL-S, IMPA, and 1-SN. Analysis of variance and Tukey's test were applied for measurements H.SN, Cx, IMPA, 1-SN, MLA, and NLA, whereas Kruskal-Wallis and Dunn's tests were applied for UL-S and LL-S. RESULTS: The results showed statistically significant differences for the measurements H.SN, Cx, UL-S, and IMPA between Groups I, II-1 and II-2 (p < 0.05). Measurements LL-S and MLA showed statistically significant difference between Groups I and II-1 only (p < 0.05). On the other hand, no statistically significant differences were found for measurement NLA among the 3 groups (p < 0.05). CONCLUSION: Regarding facial characteristics expressed by measurements H.SN, Cx, and UL-S, one could conclude that Class II division 1 and Class II division 2 malocclusions, both differed from Class I malocclusion. In addition, Class II division 1 malocclusion was found to have facial characteristics expressed by MLA, which differentiate it from the Class II division 2 and Class 1 malocclusions. Class I, Class II division 1 and Class II division 2 malocclusions showed no difference in facial characteristics expressed by the measurement NLA, and measurement LL-S was directly related to eversion of the lower lip.